Parameter demografi Opius chromatomyiae (Hymenoptera: Braconidae) pada lalat pengorok daun Liriomyza Huidobrensis (diptera: agromyzidae) - Rusli Rustam; Aunu Rauf; Nina Maryana; Pudjianto Pudjianto; Dadang Dadang (Jurnal Entomologi Indonesia, 2007)
Opius chromatomyiae (Hymenoptera: Braconidae) is an endoparasitoid attacking leafminers in the field. The objective of the research is to study the statitiscal demographic of the parasitoid. Result showed that female lifespan (9.95 days) was shorter than male (11.73). Female fecundity was about 104.73 eggs. with rate of egg production per day was about 9.31 eggs. This parasitois was also found to be female-biased sex ratio. Regarding population parameter, net reproduction rate (Ro) was about 28.55, of increase (λ) 1.23. The stable age of Opius chromatomyiae was about 37.93% eggs, 24.92 % larval, 20.36 % pupae and 16.78 % adult.